INTEGRATED ENGLISH LEARNING PROGRAM TO HELP STUDENTS PRODUCE SIMPLE AND COMPLEX SENTENCES - Firmansyah Diyata (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
This paper tells about an integrated English learning program that consists of some grammar materials in English that are considered to be able to help students with low level English background create simple and complex sentences. The materials presented in this learning program help the students to comprehend each part that a sentence has, both in simple or complex ones. The integrity of this learning program is put on how it shows the students that understanding the sentence from its subject will siginificantly lead them to know how to decide the predicte of that sentence, so that they can create a complete sentence with correct grammatical rules. This ability of creating the sentences indirectly also lead the students to understand an English subtitled reference. By understanding each sentence in an English subtitled reference, students automatically will be able to comprehend its main idea. Comprehending each main idea in all paragraphs in a text means the students will be able to know the content of the text. Besides that, this learning program is also believed to be able to facilitate students with no English background to start building their English foundation.